2019
DOI: 10.1111/his.13973
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal adenocarcinoma with enteroblastic differentiation: a clinicopathological study of five cases

Abstract: Aims Colorectal adenocarcinoma with enteroblastic differentiation (CAED) is a rare malignancy, and its clinicopathological characteristics have not yet been fully elucidated. This study aimed to elucidate the clinicopathological features of CAED through immunostaining of enteroblastic lineage markers alpha‐fetoprotein (AFP), glypican‐3 (GPC3), and spalt‐like transcription factor 4 (SALL4). Methods and results We identified five CAED cases (0.3%) from 1666 colorectal carcinomas, analysed the clinicopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Our group has previously reported five cases of pure CAED among 1666 CRC, 12 but this study did not include all the cases of CAED because these five cases were selected from electronic pathological case files by searching for keywords related to enteroblastic differentiation. In addition to the recently diagnosed cases of pure CAED between 2016 and 2018, 12 we have identified a further 10 cases of pure CAED. Among these, six cases had vascular invasion, six had lymph node metastasis and five had distant metastasis or peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group has previously reported five cases of pure CAED among 1666 CRC, 12 but this study did not include all the cases of CAED because these five cases were selected from electronic pathological case files by searching for keywords related to enteroblastic differentiation. In addition to the recently diagnosed cases of pure CAED between 2016 and 2018, 12 we have identified a further 10 cases of pure CAED. Among these, six cases had vascular invasion, six had lymph node metastasis and five had distant metastasis or peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…p53 overexpression was an adverse prognostic factor in the 42 cases of CAED ( Figure 2H,I), and this was in accordance with previous reports describing the prognostic value of TP53 status in conventional CRCs. 28,29 According to previous reports, 2,12,15 the existence of clear cytoplasm and the expression of at least one of the oncofetal proteins as enteroblastic markers are necessary for the diagnosis of gastrointestinal adenocarcinoma with enteroblastic differentiation. We have previously shown that there was no difference in clinicopathological and molecular characteristics based on the presence of tumour cells with clear cytoplasm in GAED, and we proposed that classical hepatoid adenocarcinoma could be grouped together as GAED based simply on the expression of enteroblastic markers, regardless of the presence of clear cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations